2008
DOI: 10.1007/s11356-008-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of urban inhalation exposures to benzene, formaldehyde and acetaldehyde in the European Union

Abstract: To reduce exposures and consequent health effects, adequate measures must be taken to diminish emissions from sources such as materials and products that especially emit benzene and formaldehyde in indoor air. In parallel, measures can be taken aiming at reducing the outdoor pollution contribution indoors. Besides emission reduction, mechanisms to effectively monitor and manage the indoor air quality should be established. These mechanisms could be developed by setting up appropriate EU indoor air guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 30 publications
2
37
1
2
Order By: Relevance
“…It is also regarded as an important source of indoor pollution: smoking has been identified as the major indoor source of benzene, contributing an average of 2-3 μg/m 3 to total indoor air concentrations (Ilgen et al, 2001a). The ranges of benzene (1-30 μg/m 3 ) reported in this study were similar to those reported by Bruinen de Bruin et al (2008), but higher than those measured by Guo et al (2003) (Table 7). Tables 8 and 9 show the lifetime health risks of carcinogens and non-cancer pollutants.…”
Section: Monitoring Of Formaldehyde and Vocssupporting
confidence: 81%
See 1 more Smart Citation
“…It is also regarded as an important source of indoor pollution: smoking has been identified as the major indoor source of benzene, contributing an average of 2-3 μg/m 3 to total indoor air concentrations (Ilgen et al, 2001a). The ranges of benzene (1-30 μg/m 3 ) reported in this study were similar to those reported by Bruinen de Bruin et al (2008), but higher than those measured by Guo et al (2003) (Table 7). Tables 8 and 9 show the lifetime health risks of carcinogens and non-cancer pollutants.…”
Section: Monitoring Of Formaldehyde and Vocssupporting
confidence: 81%
“…The inhalation exposure of individuals depends on personal time allocated to daily activities in different microenvironments (Bruinen de Bruin et al, 2008). A more complete picture of human inhalation exposure and factors determining this exposure can be obtained by combining the daily activity and microenvironment monitoring data (Sexton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de los estudios han reportado concentraciones por abajo del límite máximo permisible (Cuadro VII). Las principales fuentes de formaldehído se encuentran Gilbert et al 2006, Ohura et al 2006, de Bruin et al 2008, por eso una buena ventilación disminuiría la concentración. Si por el contrario, la concentración en la atmósfera fuera mayor, ésta aumentaría en el interior.…”
Section: Discussionunclassified
“…Thus, it is in these cases where humidity interference on measurements should be addressed. Areas with concentrations of benzene above the annual limit value are widely reported in the literature (Anttila et al, 2016;Bruinen De Bruin et al, 2008;Licen et al, 2016;Al Madhoun et al, 2011).…”
Section: Influence Of Humidity On Benzene Measurementsmentioning
confidence: 99%